Entering the third decade of experience with octreotide LAR in neuroendocrine tumors: A review of current knowledge. Issue 2 (April 2019) - Pusceddu, Sara; Prinzi, Natalie; Raimondi, Alessandra; Corti, Francesca; Buzzoni, Roberto; Di Bartolomeo, Maria; Seregni, Ettore; Maccauro, Marco; Coppa, Jorgelina; Milione, Massimo; Mazzaferro, Vincenzo; de Braud, Filippo
Gastroenteropancreatic neuroendocrine tumors (NETs) are a relatively rare group of heterogeneous neoplasms. The most significant advance in therapy of NETs has been the advent of the somatostatin analog octreotide, which represents a cornerstone in their management and dramatically changed the therapeutic landscape. Octreotide long-acting release (LAR) was developed to overcome some of the limitations of octreotide. Several clinical studies, including PROMID and RADIANT-2, have validated the clinical benefits of octreotide LAR in NETs, with tumor shrinkage in about 10% of patients and tumor stabilization in roughly half of cases. While the use of octreotide LAR is well-consolidated in NETs, some open questions remain. These include the use of high-dose octreotide LAR, as there is evidence that higher dose may provide longer disease control, and nonstandard treatment schedules, with administration every 21 days instead of 28 days, as well as their use in combination with targeted agents or peptide receptor radiotherapy in clinical practice. After 3 decades of clinical experience with octreotide LAR, the drug has a well-established safety profile. It is well-tolerated and treatment discontinuations due to adverse events are uncommon. One exception is cholelithiasis, which may increase with longer duration of treatment. According to the literature data, octreotide LAR is currently recommended in both functioning and nonfunctioning advanced NETs. This review summarizes the available clinical data with octreotide LAR and also provides future perspectives on its possible uses in patients with NETs.